PENGARUH MANAGEMENT CONTROL SYSTEM TERHADAP INTELLECTUAL CAPITAL MELALUI IMPLEMENTASI ERP PADA PERUSAHAAN YANG MENERAPKAN SISTEM ERP DI INDONESIA - Handry Adhi Prawira; Saarce Elsye Hatane; Priskila Adiasih (Business Accounting Review, 2018)
Intellectual capital that is owned by a company is considered as one of the strategic asset, which is important for the success and sustainability of the company, in a business competitive environment. This study aimed to identify whether interactive control system and diagnostic control system, which were parts of management control system, were able to increase the intellectual capital of a company with ERP implementation as an intervening variable so it could be a source of competitive advantage for the company.This study that was conducted on 57 respondents from 36 companies that implemented ERP system in Indonesia, showed that there was positive and significant relationship of management control system to intellectual capital through ERP implementation as the intervening variable